2004
DOI: 10.1128/jvi.78.10.5244-5257.2004
|View full text |Cite
|
Sign up to set email alerts
|

CD4+T Cells from CD4C/HIVNefTransgenic Mice Show Enhanced Activation In Vivo with Impaired Proliferation In Vitro but Are Dispensable for the Development of a Severe AIDS-Like Organ Disease

Abstract: The cellular and molecular mechanisms of dysfunction and depletion of CD4 ؉ T lymphocytes over the course of human immunodeficiency virus type 1 (HIV-1) infection are still incompletely understood, but chronic immune activation is thought to play an important role in disease progression. We studied CD4 ؉ T-cell biology in CD4C/HIV transgenic (Tg) mice, in which Nef expression is sufficient to induce a severe AIDS-like disease including a preferential decrease of CD4 ؉ T cells. We show here that Nef-expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
61
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 73 publications
13
61
0
Order By: Relevance
“…Studies by Jolicoeur and coworkers (19) in CD4C/HIV-Nef tg mice have shown similar thymic depletion and increased peripheral T cell activation and proliferation as we report here. To test whether this increased activation was TCR dependent, these investigators crossed their Nef tg mice with TCR tg mice (AD10).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Studies by Jolicoeur and coworkers (19) in CD4C/HIV-Nef tg mice have shown similar thymic depletion and increased peripheral T cell activation and proliferation as we report here. To test whether this increased activation was TCR dependent, these investigators crossed their Nef tg mice with TCR tg mice (AD10).…”
Section: Discussionsupporting
confidence: 74%
“…Upon viral challenge with vesicular stomatitis virus and lymphocytic choriomeningitis virus, it appeared that Nef tg T cells were less capable of inducing virusspecific CTL responses and to clear the virus (15). In line with this finding, Nef tg T cells had decreased in vitro proliferative capacities compared with wild-type (wt) T cells (15,18,19).…”
Section: T Cell Activation and Proliferation Characteristic For Hiv-nefsupporting
confidence: 71%
See 3 more Smart Citations